ANALISIS SEGMEN PASAR DAN PERILAKU NASABAH TERHADAP BANK SYARIAH DI WILAYAH DKI JAKARTA - RR. Kathrin Irviana; Rita Nurmalina; Arif Imam Suroso (Jurnal Manajemen & Agribisnis, 2008)
The purpose of this research is for identifying market segment and customer behavior toward Islamic Banking and its marketing implications in all regions of DKI Jakarta. The research was conducted on August – October 2008 in East, West, North, South and Central of Jakarta. The survey was conducted by doing face to face interview and questionaires distribution to 120 proportional responden. The analytical tools applied are analysis of cluster, factor & descriptive and using SPSS version 11.5 as the statistic’s tool. The result of this research for segmentation aspect showed the characteristics and size of each market segment of Islamic banks. The market segment consists of syariah loyalist, floating mass and conventional loyalist. From this research, floating mass segment has been showed that this segment is the most potential segment among others in DKI Jakarta regions due to it has the largest target market compared to syariah loyalist and conventional loyalist segments. However responden with Islam as their religion are still priority target market for Islamic banks since floating mass responden have been collected from Islamic’s responden dominantly with employees and entrepreneurs as the occupations.  Further, market segment will be analyzed in relation with customers’ category, region of geography, religion and occupation. In customer behavior side, customers preferences and information resources toward Islamic banks will be the important factors which could influence customers behavior when choosing Islamic banks. The four factors influence customers in choosing Islamic banks are  building physical’s appearance, ATM network, variety of products and profit rate. Both results of market segmentation and consumer behavior toward Islamic Banking are important factors for Islamic Banking in formulating marketing strategy.